2019
DOI: 10.1261/rna.068288.118
|View full text |Cite
|
Sign up to set email alerts
|

Predictive models of subcellular localization of long RNAs

Abstract: Export to the cytoplasm is a key regulatory junction for both protein-coding mRNAs and long noncoding RNAs (lncRNAs), and cytoplasmic enrichment varies dramatically both within and between those groups. We used a new computational approach and RNA-seq data from human and mouse cells to quantify the genome-wide association between cytoplasmic/ nuclear ratios of both gene groups and various factors, including expression levels, splicing efficiency, gene architecture, chromatin marks, and sequence elements. Splic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 76 publications
5
79
3
Order By: Relevance
“…An analysis of lncRNA in TEX-treated human tumor cells provided similar results with a dominance of chromosome modulation, followed by miRNA sponging, engagement in protein complex formation frequently including RBP and being involved in splicing and translation, and least frequently in transcription initiation. Finally, the vast majority of these lncRNAs are engaged in several functions, which is well in line with lncRNA shuttling between the nucleus, mitochondria, and cytoplasm [82,[122][123][124][125][126].…”
Section: Lncrna Shuttling: Melding and Resolving The Distinct Ev Actimentioning
confidence: 76%
“…An analysis of lncRNA in TEX-treated human tumor cells provided similar results with a dominance of chromosome modulation, followed by miRNA sponging, engagement in protein complex formation frequently including RBP and being involved in splicing and translation, and least frequently in transcription initiation. Finally, the vast majority of these lncRNAs are engaged in several functions, which is well in line with lncRNA shuttling between the nucleus, mitochondria, and cytoplasm [82,[122][123][124][125][126].…”
Section: Lncrna Shuttling: Melding and Resolving The Distinct Ev Actimentioning
confidence: 76%
“…We argue that cells can regulate the subcellular localization and biological functions of RNAs through alternative splicing of introns, which contain localization elements (RNA structure context or sequence motifs). These findings can help us better understand the regulatory mechanisms of RNA localization, and thus, for example, predict RNA localization more precisely from sequence characteristics [76].…”
Section: Discussionmentioning
confidence: 87%
“…According to Zhang et al's article [37], mutational analyses showed that a novel RNA pentamer sequence motif, AGCCC, mediated the nucleus localization of lncRNA BORG with a sequence limitation at positions -8 (T or A) and -3 (G or C) relative to the first nucleotide of the pentamer. On the report of Zuckerman and Ulitsky [38], the preference for C-rich hexamers correlated with nucleus enrichment. Moreover, the biological mechanism of CG-contented octamer trimodal spectrum was unique [39].…”
Section: B Feature Representation 1) K-mer Nucleotide Composition Fementioning
confidence: 90%